Effects of Pupils’ Perceptions towards School Uniform on Learners’ Self-Esteem - Catherine, Sempele NL; Mugalavai , Violet K (Nurture, 2012)
Clothing which includes school uniform is likely to influence one’s body image perceptions. This study looked at the effects of pupils’ perceptions towards school uniform on learners’ self-esteem. The objective of the study was to investigate pupils’ perceptions towards school uniform and the effect this has on learners’ self-esteem. The hypothesis there is no significant relationship between school uniform and learners’ self-esteem as perceived by pupils guided this study. Purposive and stratified sampling techniques were used to identify and select pupils from classes 5, 6, 7 and 8 to participate in the study. These are pupils aged between 10 and 16 years old in their adolescence stage of growth and development thus in the process of establishing their personality. The researchers used questionnaires and focus group discussions to collect the information required. The sample comprised of 248 pupils attending public primary schools in Marigat Division of Baringo County in Kenya. Descriptive statistics was used to analyze the data and the relationship and difference between variables was established using the Chi-square, correlation and the Anova analysis. The study established that based on perceptions towards school uniform, pupils significantly related school uniform to learners’ self-esteem although there was no significant difference in perception by gender.